Potential Management of Nusakambangan Island as a Special Area for Rehabilitation and a National Defense and Security Zone - Heru Yoga Pamungkas; Adnan Madjid; Irwan Triadi; Pujo Widodo; Achmed Sukendro (Dinasti Research, 2024)
As an area restricted solely to the execution of penal functions, research interests, and mining activities, Nusakambangan Island primarily serves the purposes of securing and rehabilitating inmates. Consequently, the development of Nusakambangan Island should ideally focus on implementing a robust penitentiary system. Currently, however, development efforts on Nusakambangan Island are limited to constructing facilities supporting correctional institutions, overlooking its broader potential and functions for national interests. The aim of this study is to analyze the existing conditions to ascertain its potential and identify the challenges in managing Nusakambangan Island as a special area for rehabilitation, national defense, and security. The research methodology employed is qualitative, utilizing a participatory observation approach with full participation. Primary data was gathered through direct observation by the researcher, while secondary data was obtained through a juridical normative approach. The findings reveal that annual population migration into the Nusakambangan area is increasingly uncontrollable, sedimentation issues in the Segara Anakan area lack clear management, ongoing debates over island management persist, and the Directorate General of Corrections' limited authority over Nusakambangan Island exacerbates these complex issues. To optimize the penitentiary system, it is recommended that Nusakambangan Island be designated as a proportionally closed special area solely open for research, protected forests, and mining interests under clear policy directives.